1976
DOI: 10.1254/jjp.26.145
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Connections Between Locus Coeruleus and Cerebral Cortex

Abstract: Abstract-Small tracking electrodes were inserted into the cat locus eoeruleus (LC), and the effects of LC stimulation were determined on the transcallosal potential (TCP) evoked in cerebral cortex on the same side. LC stimulation at 8 volts inhibited TCP amplitude an average of II Rostral LC placements appeared most effective. LC stimulation, without drugs, did not affect the peak latency of the TCP. dl-Propranolol and FLA-63 blocked LC inhibition of the TCP and also increased TCP amplitude per se. Propranolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 23 publications
(19 reference statements)
1
0
0
Order By: Relevance
“…Hoffer et al (9) found that discrete stimulation of LC decreased the spontaneous discharge rate of cerebellar Purkinje cells through noradrenaline mediated mechanism. Similar inhibitory effects of LC stimulation on hippocampal pyra midal cells (10), relay neurons of the spinal trigeminal nucleus (11) and the transcallosal potential in cerebral cortex (12) have also been found. However, electrophysiological evidence for the role of LC in modulating the amygdaloid activity has apparently not been reported.…”
supporting
confidence: 53%
“…Hoffer et al (9) found that discrete stimulation of LC decreased the spontaneous discharge rate of cerebellar Purkinje cells through noradrenaline mediated mechanism. Similar inhibitory effects of LC stimulation on hippocampal pyra midal cells (10), relay neurons of the spinal trigeminal nucleus (11) and the transcallosal potential in cerebral cortex (12) have also been found. However, electrophysiological evidence for the role of LC in modulating the amygdaloid activity has apparently not been reported.…”
supporting
confidence: 53%